Transcriptomic signatures of transfer cells in early developing nematode feeding cells of Arabidopsis focused on auxin and ethylene signaling - Cabrera, Javier; Barcala, Marta; Fenoll, Carmen; Escobar, Carolina (Frontiers in Plant Science, 2014)
Phyto-endoparasitic nematodes induce specialized feeding cells (NFCs) in their hosts, termed syncytia and giant cells (GCs) for cyst and root-knot nematodes, respectively. They differ in their ontogeny and global transcriptional signatures, but both develop cell wall ingrowths to facilitate high rates of apoplastic/symplastic solute exchange showing transfer cell (TC) characteristics. Regulatory signals for TC differentiation are not still well known. The two-component signalling system (2CS) and reactive oxygen species are proposed as inductors of TC identity, while, 2CSs-related genes are not major contributors to differential gene expression in early developing NFCs. Additionally, transcriptomic and functional studies have assigned a major role to auxin and ethylene as regulatory signals on early developing TCs. Genes encoding proteins with similar functions expressed in both early developing NFCs and typical TCs are putatively involved in upstream or downstream responses mediated by auxin and ethylene. Yet, no function directly associated to the TCs identity of NFCs, such as the formation of cell wall ingrowths is described for most of them. Thus we reviewed similarities between transcriptional changes observed during the early stages of NFCs formation and those described during differentiation of TCs to hypothesize about putative signals leading to TC-like differentiation of NFCs with particular emphasis on auxin an ethylene.